ON-LINE BUYING BEHAVIOR OF CONSUMERS WITH REFERENCE TO KRISHNAGIRI DISTRICTS - R. Usha; S. M. Krishnan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Information technology and its evolution play a predominant place in the success of business in diverse market environments. It provides unique information about world business opportunities. In such a way websites are becoming mainstream commercial usages as it is user-friendly for every walk of life. The internet is the technology introduced in the modern field of business, which is widely used for business operations. Based on usage, internet users are classified into two categories according to their nature such as active and passive users. The active users are those who use selective search engines and refer to some websites for the collection of information for purchasing goods and services. [1] passive users are those who receive frequent messages through their e-mail, social media, or other modes of message about the availability of products in the markets. Likewise, from the buyer’s point of view, buyers are divided into two categories online and offline. The online purchasing of goods and commodities with help of online sources or retailers such as Flipkart, Amazon, Grofers India Pvt. Ltd, Zomato Ltd, Myntra Designs Pvt. Ltd etc., offline buyers depend on dependable marketers, like retailers, wholesalers, agents, etc.